2014
DOI: 10.1586/14737167.2014.957185
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profile of breast cancer: cost–effectiveness analysis from the Spanish National Healthcare System perspective

Abstract: Background: Cost-effectiveness analysis of MammaPrint ® in the diagnosis of early breast cancer.Material and methods: Markov model assuming a cohort of 60-year-old women with breast cancer. Treatment costs and effects were assessed by comparing the 5-year,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…Budget impact was mentioned in terms of the specific treatment or associated testing and how this may potentially inhibit the uptake and use of these interventions in clinical practice. Three studies focused on the budget impact in broad terms [4143], but a further ten studies specified the discussion about the financial impact of testing or treatment [42, 4452].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Budget impact was mentioned in terms of the specific treatment or associated testing and how this may potentially inhibit the uptake and use of these interventions in clinical practice. Three studies focused on the budget impact in broad terms [4143], but a further ten studies specified the discussion about the financial impact of testing or treatment [42, 4452].…”
Section: Resultsmentioning
confidence: 99%
“…However, clinical practice is complex and the way in which a test fits into the current care pathway is not always clear. Nine studies highlighted issues with the transition of tests from research to clinical settings [41, 42, 54, 55, 60–64]. For example, Breijer et al [61] developed and evaluated two multivariable models to produce an algorithm to predict the risk of endometrial cancer based on patients’ characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of pivotal clinical trials of CDK4/6 inhibitors (MONALEESA-2 and PALOMA-2), 8 , 12 average age was 62 years, with an estimated mean body surface of 1.7 m 2 . 13 , 14 …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, just like the studies that used monitoring data, all economic evaluations were performed after development. Seven studies reported increased effects , 88 , 90–93 , 96 , 97 and 6 studies reported that use of analytics would increase costs. 90 , 93–95 , 97 , 98 All but 1 study included the costs of the analytics or the test in which the analytics were implemented.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported increased effects , 88 , 90–93 , 96 , 97 and 6 studies reported that use of analytics would increase costs. 90 , 93–95 , 97 , 98 All but 1 study included the costs of the analytics or the test in which the analytics were implemented. 89 Moreover, unlike the other categories, several papers discussed price thresholds at which the analytics or the test would be cost-neutral or dominant (ie, more effects and lower costs) or thresholds at which the analytics or test would be cost-effective (ie, where the incremental cost-effectiveness ratio would be below a specific cost-effectiveness threshold).…”
Section: Resultsmentioning
confidence: 99%